City Branding Kota Bandung Melalui Instagram @disbudpar.bdg - Farhani, Rafa Nabilah; Tresnawaty, Betty; Ma’arif, Abdul Aziz (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This research purposes to get an overview of the formation of city branding carried out by the Bandung City Culture and Tourism Office through Instagram @disbudpar.bdg. This research uses a constructivistic paradigm with descriptive methods. Data were collected through interviews, observation, and documentation. The results showed that the Office of Culture and Tourism of Bandung City formed city branding with four steps, including creating core brand values, namely creative values and emotional values, creating core brand messages, namely creative tourism cities and utilization of Instagram @disbudpar.bdg, determining brand personalities which include city leaders as city symbols and creative cities by design, and determining brand icons, namely analysis of the Stunning Bandung logo.